Factors Influencing ICT Adoption Among University Students in Morocco - Soumia El Hazzat; Yamina EL KIRAT EL ALLAME; Rdouan FAIZI (Moroccan Journal of Quantitative and Qualitative Research)
Higher education institutions around the world have recently begun to embrace the current global technological shift by integrating Information and Communication Technologies (ICT) in different aspects of higher education including teaching, learning and administrative management. However, integrating ICT into higher education is a complex process often hindered by numerous challenges. This study aims to examine the factors influencing ICT adoption among students in Moroccan universities by addressing two research questions: (1) what are the main barriers that prevent students from effectively using ICT in their learning? (2) What factors motivate students to use ICT in their educational activities? The study adopts a mixed methods approach combining qualitative and quantitative data. A questionnaire was administered to a sample of 354 students across 12 universities in Morocco. Qualitative data was gathered from 140 of the same sample. Data analysis and interpretation confirmed that most students face significant barriers related to ICT use including inadequate ICT support and infrastructure, lack of technology-related training, and frequent connectivity issues. The strongest motivators for ICT use among students include the availability of resources, improvements to ICT infrastructure, and the practical benefits of ICT, such as ease of access to information, increased productivity and efficiency, and ease of use.